Efektifitas Hypnobreastfeeding pada Produksi ASI - Suprida Suprida; A. Kadir; Eka Masfira (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2021)
Breastfeeding is one of the main task of mother in meeting the nutritional needs of her baby, but the success of exclusive breastfeeding in Palembang Regency was low ( 72 % ) because the failure of first breastfeeding for the babies and also because factors obstruct mother didn’t want to brasfeeding. First incessant produser campaign for milk and food replace ASI. Second, lack of cognition mother about giving food to child. Third, not care really from experts health to promote habit breasfeeding child. Forth, lack of program social welfare evident, which is conducted by several goverment agency.one of solution to help overcome it is hypnobreasfeeding. This research is study preexperiment with approach one group pretest posttes. Technique taking sample use perposive sampling in the puerperal mother with the number 30 person. This research conducted in april-june. statistic test use wilcoxon test. The results processing data with use wilcoxon test against expenditure ASI in the puerperal mother before and after intervetion, the results obtained sicnificancy r = 0,000 (r< 0,05) which mean there is influence technique hypnobreasfeeding against expenditure ASI in the puerpural mother. The conclution from this research there is influence technique hypnobreasfeeding against expenditure ASI in the puerperal mother in BPM Husniyati and BPM Yuhana at palembang city 2018.